Computed tomographic perfusion abnormalities in acute migraine with aura: Characteristics and comparison with transient ischemic attack. (December 2022) - Strambo, Davide; Nannoni, Stefania; Rebordão, Leonor; Dunet, Vincent; Michel, Patrik
Introduction: Migraine with aura (MA) accounts for up to 10% of "stroke mimics" and can present cerebral perfusion abnormalities. We aimed to compare perfusion-CT (PCT) findings in acute-onset MA mimicking an ischemic stroke with those observed in transient ischemic attack (TIA). Methods: We retrospectively studied patients admitted to our hospital between 2002 and 2014 with suspicion of acute ischemic stroke, having PCT and receiving a final diagnosis of MA. We visually assessed PCT for the presence and extent of focal hypoperfusion (FHP). MA patients with FHP were compared with consecutive TIA patients showing FHP. We performed both qualitative and quantitative analysis of PCT. Results: Of 47 patients with MA (median age = 33 years, 55% females), 16 (34%) displayed FHP. Compared to MA patients without FHP, MA patients with FHP had similar headaches and aura features, but a less frequent history of MA ( p = 0.010). Compared to 74 TIA patients with FHP (median age = 69 years, 43% females), MA patients with FHP showed hypoperfusion that more frequently involved adjacent vascular territories or a whole hemisphere ( p < 0.001). In addition, hypoperfusion in MA patients had a less pronounced increase in rMTT (1.2 vs 1.8, p < 0.001) and rTTP (1.1 vs 1.2, p < 0.001), and a lesser decrease in rCBF (0.8 vs 0.6, p < 0.001) compared to hypoperfusion in TIA. rMTT displayed the best discriminative ability to differentiate MA from TIA. Conclusion: Focal perfusion abnormalities in acute MA often involve adjacent vascular territories and hypoperfusion is less pronounced than in TIA. MA can be best differentiated from TIA by a smaller rMTT increase.